Brain abscess with pyogenic ventriculitis. (2022) - Feinberg, Nina; Campbell, Brendan; Bazylewicz, Michael; Brown, William D.; Singh, Devika; Whitman, Timothy; Alston, W. Kemper; Ulano, Adam; Sawatzky, Benjamin; Hale, Andrew J.
Abstract: The authors present the case of a 57-year-old male with a large polymicrobial brain abscess complicated by eruption into the intraventricular space. He was treated with parenteral ampicillin, cefepime, and metronidazole and adjuvant intraventricular vancomycin/gentamicin as well as surgical debridement. The authors discuss the diagnosis, treatment, and prognosis of brain abscesses, with a focus on prior cases with pyogenic ventriculitis and those treated with intraventricular antimicrobials.